2015
DOI: 10.1016/j.bpj.2015.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Heterogeneity in Response of Cells Expressing a Fluorescent Hydrogen Peroxide Biosensor

Abstract: Fluorescent, genetically encoded sensors of hydrogen peroxide have enabled visualization of perturbations to the intracellular level of this signaling molecule with subcellular and temporal resolution. Ratiometric sensors hold the additional promise of meaningful quantification of intracellular hydrogen peroxide levels as a function of time, a longstanding goal in the field of redox signaling. To date, studies that have connected the magnitudes of observed ratios with peroxide concentrations have either examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…In fact, the character of this dependence indicates that in H 2 O 2 -exposed cells, HyPer reduction cannot be considered as a reaction of pseudo-first order, and its rate is dependent on the level of reduced HyPer-interacting enzymes, which may be depleted after H 2 O 2 exposure. For instance, recent theoretical considerations have shown that depletion of the reduced form of glutaredoxin can affect HyPer oxidation after a bolus exposure of HeLa cells to 20 μM of H 2 O 2 [21]. In addition, we suggest that the level of reduced thioredoxins can also be lowered in the H 2 O 2 -exposed cells due to the massive reduction of oxidized peroxiredoxins [22].…”
Section: Discussionmentioning
confidence: 75%
“…In fact, the character of this dependence indicates that in H 2 O 2 -exposed cells, HyPer reduction cannot be considered as a reaction of pseudo-first order, and its rate is dependent on the level of reduced HyPer-interacting enzymes, which may be depleted after H 2 O 2 exposure. For instance, recent theoretical considerations have shown that depletion of the reduced form of glutaredoxin can affect HyPer oxidation after a bolus exposure of HeLa cells to 20 μM of H 2 O 2 [21]. In addition, we suggest that the level of reduced thioredoxins can also be lowered in the H 2 O 2 -exposed cells due to the massive reduction of oxidized peroxiredoxins [22].…”
Section: Discussionmentioning
confidence: 75%
“…We observed that HyPer’s ratio increased to its peak value for that H 2 O 2 concentration within the first 2 min post bolus addition, followed by a gradual decrease back to the baseline (Supplementary Figure S1). Because the kinetics of the fluorescence signal are determined by the slow conformational change of oxidized HyPer and its reduction by a limited pool of glutaredoxin, a delay exists between the cytosolic H 2 O 2 changes and the resulting signal output of HyPer . Therefore, we assumed that the peak of each HyPer kinetic curve corresponds to the maximum cytosolic H 2 O 2 concentration during bolus addition, with a time lag due to the conformational change of the sensor.…”
mentioning
confidence: 99%
“…This could be explained by the high H 2 O 2 generation in the ER during insulin biosynthesis that oxidizes HyPer by leaving the ER lumen. Generally, the maximal Hyper ratio after H 2 O 2 perifusion depends on the basal oxidation status of the HyPer protein that correlates with the oxidation level of the observed compartment [ 58 ]. AQP8 overexpression shows a faster HyPer response compared to mock cells at the cytosolic face of the ER membrane indicating a faster H 2 O 2 influx through the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%